Prospek Regionalisme Timur-Tengah Pasca-Arab Spring: Telaah terhadap Identitas Kolektif Liga Arab - Ziyad Falahi (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2012)
Several large demonstrations have taken place all over the world in recent years, especially arab spring is a revolutionary wave of protests, and wars occurring in the middle east that. Therefore, this paper try to elaborate the prospect of regionalism in Middle-east after Arab Spring occured. Some academician believed that the dramatical transtition of political regime in middle east can be enable a more deeper integration of arab league than before. But along to the history, the integration of Arab league always restraint because of the absence of collective identity. Indeed, one of the most impotant thing to determine regionalism is collective identity. Collective identity cant be easily constructed when the member still have a misperception among the others. On the other hand, the transformation of global economics push the appearance of south south cooperation. This condition could be push a economic cooperation among arab league members as a first step in institutionalization process.Keyword: Collective Identity, Arab league, Arab Spring, Regionalism, and South-South Cooperation.